EKSISTENSI WHITE COLLAR CRIME DI INDONESIA - Auliah Anriani Pohan; Suci Annisa Pangesti; Siti Nuraida; Sahlan Batubara (Yayasan Pendidikan Islam dan Multikultural, 2023)
Abstract: This paper discusses about the existence of ‘white collar crime’ in Indonesia. The ‘white collar crime’ will always exist because of many factors, such as: culture, learning-process about corruption, and human element to do a mistake and greed. It is an extra-ordinary crime in Indonesia that needs holistic and extra-ordinary actions from the government, citizens, and apparatus to combat.